2022
DOI: 10.3390/biomedicines10030660
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles Derived from Acidified Metastatic Melanoma Cells Stimulate Growth, Migration, and Stemness of Normal Keratinocytes

Abstract: Metastatic melanoma is a highly malignant tumor. Melanoma cells release extracellular vesicles (EVs), which contribute to the growth, metastasis, and malignancy of neighboring cells by transfer of tumor-promoting miRNAs, mRNA, and proteins. Melanoma microenvironment acidification promotes tumor progression and determines EVs’ properties. We studied the influence of EVs derived from metastatic melanoma cells cultivated at acidic (6.5) and normal (7.4) pH on the morphology and homeostasis of normal keratinocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 91 publications
1
13
0
9
Order By: Relevance
“…Aware of the importance of translating this study in vivo, we plan to validate our results by using a model of experimental metastasis in syngeneic mice. In line with our observations, very recently, Bychkov and colleagues demonstrated that extracellular acidosis, via inducing metastatic melanoma cells to release EV with advanced pro-tumoral activity, sustained the acquisition of an increased malignant phenotype of melanoma cells themselves, also redirecting keratinocytes towards pro-tumoral activities [ 45 ]. This preclinical in vitro study allowed us to identify another mechanism through which the acidic TME may foster tumor progression and dissemination, exploiting the great potential of EV to convey pro-tumoral molecular signals capable of altering the microenvironment of secondary locations and prepare for metastatic colonization.…”
Section: Discussionsupporting
confidence: 87%
“…Aware of the importance of translating this study in vivo, we plan to validate our results by using a model of experimental metastasis in syngeneic mice. In line with our observations, very recently, Bychkov and colleagues demonstrated that extracellular acidosis, via inducing metastatic melanoma cells to release EV with advanced pro-tumoral activity, sustained the acquisition of an increased malignant phenotype of melanoma cells themselves, also redirecting keratinocytes towards pro-tumoral activities [ 45 ]. This preclinical in vitro study allowed us to identify another mechanism through which the acidic TME may foster tumor progression and dissemination, exploiting the great potential of EV to convey pro-tumoral molecular signals capable of altering the microenvironment of secondary locations and prepare for metastatic colonization.…”
Section: Discussionsupporting
confidence: 87%
“…For example, incubation of keratinocytes with EVs derived from metastatic melanoma cells activates the AKT/mammalian target of rapamycin (mTOR) and extracellular-signal-regulated kinase (ERK) signaling pathways, thereby increasing cell migration ability. In addition, tumor-cell-derived EV-treated keratinocytes had a stem-like phenotype and increased expression of SNAI1 , KLF , and CD133 factors that trigger and maintain EMT [ 34 ]. Migration-enhancing morphological changes—namely, an increase in cell length and the number of filopodia—were also observed in normal lung epithelium BEAS-2B cells after the addition of exosomes from non-small lung carcinoma cell line H1299 [ 35 ].…”
Section: Influence Of Evs Of Tumor Cells On the Normal Cellsmentioning
confidence: 99%
“…Для удаления эндогенных экзосом эмбриональную телячью сыворотку центрифугировали (70 мин, 120000 g), после чего фильтровали и смешивали со средой. Кератиноциты человека Het-1A (ATCC, США) культивировали в среде BEBM (Lonza, Швейцария) как описано ранее [7]. Внеклеточные везикулы выделяли из клеток метастатической меланомы как в [7]: клетки выращивали в среде без экзосом, культуральную среду центрифугировали последовательно при 10000 g (15 мин, 4°C) и при 120000 g (70 мин, 4°С).…”
Section: экспериментальная частьunclassified
“…Кератиноциты человека Het-1A (ATCC, США) культивировали в среде BEBM (Lonza, Швейцария) как описано ранее [7]. Внеклеточные везикулы выделяли из клеток метастатической меланомы как в [7]: клетки выращивали в среде без экзосом, культуральную среду центрифугировали последовательно при 10000 g (15 мин, 4°C) и при 120000 g (70 мин, 4°С). Белковые комплексы удаляли с помощью гель-фильтрации, используя сорбент Superdex G-250 (GE Healthcare, США).…”
Section: экспериментальная частьunclassified
See 1 more Smart Citation